Risk and Prognosis of Secondary Bladder Cancer After Radiation Therapy for Rectal Cancer: A Large Population-Based Cohort Study - Guan, Xu; Wei, Ran; Yang, Runkun; Lu, Zhao; Liu, Enrui; Zhao, Zhixun; Chen, Haipeng; Yang, Ming; Liu, Zheng; Jiang, Zheng; Wang, Xishan (Frontiers in Oncology, 2021)
Background: Although radiation therapy (RT) improves local control for rectal cancer (RC), the long-term risks from RT including development of a secondary malignancy attracted great attention. The risk and prognosis of secondary bladder cancer (SBC) in RC patients undergoing RT have not been adequately studied. To investigate the impact of RT on the risk of developing SBC and assess their survival outcomes. Methods: This large population-based study included RC patients as the first primary cancer from 9 registries of the Surveillance, Epidemiology and End Results (SEER) database between 1973 and 2015. The cumulative incidence of SBC was assessed by using Fine and Gray’s competing risk regression. The standardized incidence ratio (SIR) was used to compare the incidence of SBC in RC survivors to the US general population. The Kaplan-Meier method was used to evaluate the 10-year overall survival (OS) and 10-year cancer specific survival (CSS) for patients with SBC. Results: Of 74,646 RC patients, 24,522 patients were treated with surgery and RT and 50,124 patients were treated with surgery alone. The incidence of SBC was 1.85% among patients who received RT and 1.24% among patients who did not. The incidence of SBC in RC patients who received RT was higher than the US general population (SIR, 1.35; 95% CI, 1.19-1.53, P<0.05), but the incidence of SBC in patients who did not receive RT was similar with the US general population (SIR, 0.92; 95% CI, 0.84-1.01, P>0.05). In competing risk regression analysis, undergoing RT was associated with a higher risk of SBC (hazard ratio [HR], 1.443, 95% confidence interval [CI], 1.209-1.720; P<0.001). The results of the dynamic SIR for SBC revealed that a slightly increased risk of SBC was observed after RT in the early latency, and was significantly related to the variations of age at RC diagnosis and decreased with time progress. The 10-year OS and CSS among SBC patients after RT were comparable to SBC patients after NRT. Conclusion: Radiation was associated with an increased risk of developing SBC in RC patients, and special attention should be paid to the surveillance for these patients.